Analysis of the Use of Optical Waves in the World of Health: Literature Study - Zarkasyi, Moh Ali; Sumo, Maimon; Amin, Moh Ma’ruf; Sakinah, Sakinah; Angraini, Mila Rosa (PT. Riset Press International, 2024)
Waves are vibrations that propagate at any time. Waves are divided into two, namely mechanical waves and electromagnetic waves. In the world of health, what we often encounter are tools whose use is accompanied by one of the physics concepts, namely optical waves. Optical waves in the world of health are very important to apply because they are the basis for learning in health science or in the sense that the concepts that are developed in health science use the concept of optical waves. Optical waves are known as electromagnetic waves, because these waves describe visible light rays, infrared, and ultraviolet rays, so these rays are used as materials for the use of optical instruments. There are many kinds of optical instruments, including loupes which are used to magnify small things, microscopes as a tool to see objects that are far away with the sense of sight, binoculars as a tool to see the distance of objects that are far from the surface of the earth, and the eye as a tool for our vision. Then scientists applied the wave concept with optical tools to serve as a reference in the world of health. Waves according to Prof. Yohanes Surya, Ph. in the title of the book Vibrations and Waves (2019), propagating vibrations produce energy and move at a certain speed, and do not drag the material they pass through. The use of optical waves is widely applied in medical science, including X-rays as a detector for internal body elements to clarify broken parts such as bones or other things. From the explanation above, it can be concluded that waves are the basis in the world of health, which are of course used in optical equipment, and are a reference for the health team and as a basic concept in physics learning. This underlies the fact that optical waves are not only used in the world of education but are very It is also needed in the world of health.